Groundwater quality evaluation for irrigation application in Mandsaur region, Madhya Pradesh, India - Kulshreshtha, Vinita; Dev, Pramendra (Journal of Nepal Geological Society, 2006)
The chemical analysis of 22 water samples collected from representative open dug-wells existing in the Mandsaur area of Madhya Pradesh, India, was carried out for evaluating the quality of irrigation water. For this purpose, its colour, odour, taste, pH, total hardness, electrical conductivity, ionic concentrations, and various other parameters were determined. The calculated values of per cent sodium, Kelley's ratio, sodium adsorption ratio, residual sodium carbonate and magnesium hazard indicate that except at a few places, the groundwater, in general, is suitable for irrigation. The sodium adsorption ratio and electrical conductivity values were plotted on the U.S. Salinity Diagram. The plots of these parameters indicate that 8 samples fall in CS type (Medium Salinity and Low Sodium hazards), and 14 samples belong to C type (High Salinity and Low Sodium hazards). In general, the groundwater is favourable for irrigation use. The values of electrical conductivity and sodium percentage determined in respect of groundwater samples of Mandsaur were also plotted on the Wilcox Diagram. Based on this diagram, 4 samples represent Excellent to Good categories, whereas 18 samples indicate Good to Permissible categories. Based on this classification the groundwater of Mandsaur area, in general, is suitable for irrigation application.